A Link between Neutron and Ion Irradiation Hardening for Stainless Austenitic and Ferritic-Martensitic Steels - Boris Margolin; Alexander Sorokin; Lyubov Belyaeva (Metals, 2024)
Radiation hardening is studied for stainless austenitic and ferritic-martensitic chromium steels after ion and neutron irradiation at various temperatures. Austenitic and ferritic-martensitic steels irradiated up to 30 dpa in various nuclear reactors and ion accelerators are studied at various temperatures. A change in Vickers microhardness is used as the radiation hardening parameter. A methodology is developed that allows one to determine the ion irradiation parameters, which ensure the radiation hardening of ferritic-martensitic and austenitic steels, as close as possible to the radiation hardening of the same steels under neutron irradiation. A transferability function is introduced to connect the irradiation temperatures for ion and neutron irradiation that provides the same radiation hardening. On the basis of the obtained experimental data, after ion and neutron irradiation the transferability functions are determined for the investigated austenitic and ferritic-martensitic steels, which connect the temperatures for ion and neutron irradiation and provide the same radiation hardening at a given damage dose.